The hunger games - Collins, Suzanne (New York : Scholastic Press, 2008)
she voluntarily takes her younger sister's place.
Keywords: Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction